The Relationship between The Attitude of Mothers of Children under Five Years and Utilization of Maternal and Child Health (MCH) Handbook - Ester Simanullang; Dina Putriati; Ariska Fauzianty; Asrida Julianti Hutagalung; Rosmani Sinaga; Herna Rinayanti Manurung (Universitas Aisyah Pringsewu, 2023)
The Maternal and Child Health (MCH) handbook is a program by the Indonesian government since 1993 which is intended to provide information regarding the maintenance and care of maternal and child health. This is one of the programs proposed by the government to reduce MMR and IMR. However, the utilization of the MCH handbook is still low due to the absence of mothers’ attitudes toward the significance of the manual's contents. This study aims to determine the relationship between the attitude of mothers of children under five years and the utilization of the MCH handbook. This research is an observational analytic study with a cross-sectional approach. The sampling technique used was multistage sampling. The respondents were selected using a systematic random sampling technique, which included 45 mothers of children under five years. Furthermore, the data analysis was done using the Fisher exact test. The results of this study reported that 28 people (62.2%) had used the MCH handbook properly, while 17 people (37.8%) had not used the MCH handbook properly. Moreover, 34 people (75.6%) had a positive attitude toward using the MCH handbook, while 11 people had a negative attitude (24.4%) in using the MCH handbook. With an R-value of 0.730, there is a significant relationship between the attitude of mothers of children under five years and the utilization of the MCH handbook. It is expected that the participation of health professionals and community leaders will synergize to support mothers in taking care of their health and the health of their children, by continuing to add insight into knowledge through the use of the MCH handbook. Abstrak: Buku Kesehatan ibu dan anak (KIA) merupakan salah satu program pemerintah Indonesia sejak 1993 yang diperuntukan untuk memberikan informasi seputar pemeliharaan dan perawatan kesehatan ibu dan anak. Program ini merupakan salah satu program yang di usulkan pemerinta guna mengurangi AKI dan AKB. Pemanfaatan buku KIA masih rendah, dikarenakan minimnya sikap ibu tentang pentingnya isi buku KIA. Penelitian ini bertujuan untuk mengetahui hubungan sikap ibu balita dengan pemanfaatan buku KIA. Penelitian analitik observasional dengan pendektan cross sectional. Teknik sampling dengan multistage sampling. Responden yang dipilih menggunakan teknik systematic random sampling, berjumlah 45 ibu balita. Analisis data dengan fisher exact. Hasil penelitian ini 28 orang (62,2%) memiliki pemanfaatan buku KIA yang baik dan 17 orang (37,8%) memiliki pemanfaatan buku KIA yang buruk. 34 orang (75,6%) memiliki sikap positif dalam pemanfaatan buku KIA dan 11 orang memiliki sikap negatif (24,4%) dalam pemanfaatan buku KIA. Dengan nilai r sebesar 0,730 artinya ada hubungan yang signifikan antara sikap ibu dengan pemanfaatan buku KIA. Diharapkan, peran serta tenaga kesehatan dan tokoh masyarakat untuk bersinergi menggerakkan ibu balita agar peduli terhadap kesehatan ibu dan anaknya dengan terus menambah wawasan pengetahuan melalui pemanfaatan buku KIA